Tyrosine-610 in the Receptor Kinase BAK1 Does Not Play a Major Role in Brassinosteroid Signaling or Innate Immunity - Singh, Vijayata (Front Plant Sci, 2017)
The plasma membrane-localized BRI1-ASSOCIATED KINASE1 (BAK1) functions as a co-receptor with several receptor kinases including the brassinosteroid (BR) receptor BRASSINOSTEROID-INSENSITIVE 1 (BRI1), which is involved in growth, and the receptors for bacterial flagellin and EF-Tu, FLAGELLIN-SENSING 2 (FLS2) and EF-TU RECEPTOR (EFR), respectively, which are involved in immunity. BAK1 is a dual specificity protein kinase that can autophosphorylate on serine, threonine and tyrosine residues. It was previously reported that phosphorylation of Tyr-610 in the carboxy-terminal domain of BAK1 is required for its function in BR signaling and immunity. However, the functional role of Tyr-610 in vivo has recently come under scrutiny. Therefore, we have generated new BAK1 (Y610F) transgenic plants for functional studies. We first produced transgenic Arabidopsis lines expressing BAK1 (Y610F)-Flag in the homozygous bak1-4 bkk1-1 double null background. In a complementary approach, we expressed untagged BAK1 and BAK1 (Y610F) in the bak1-4 null mutant. Neither BAK1 (Y610F) transgenic line had any obvious growth phenotype when compared to wild-type BAK1 expressed in the same background. In addition, the BAK1 (Y610F)-Flag plants responded similarly to plants expressing BAK1-Flag in terms of brassinolide (BL) inhibition of root elongation, and there were only minor changes in gene expression between the two transgenic lines as monitored by microarray analysis and quantitative real-time PCR. In terms of plant immunity, there were no significant differences between plants expressing BAK1 (Y610F)-Flag and BAK1-Flag in the growth of the non-pathogenic hrpA(-) mutant of Pseudomonas syringae pv. tomato DC3000. Furthermore, untagged BAK1 (Y610F) transgenic plants were as responsive as plants expressing BAK1 (in the bak1-4 background) and wild-type Col-0 plants toward treatment with the EF-Tu- and flagellin-derived peptide epitopes elf18- and flg22, respectively, as measured by reactive oxygen species production, mitogen-activated protein kinase activation, and seedling growth inhibition. These new results do not support any involvement of Tyr-610 phosphorylation in either BR or immune signaling.